Effect of Serum Trace Elements, Macro-minerals and Antioxidants in Acne Vulgaris Patients: A Case-Control Study (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Acne vulgaris is a chronic skin disease with multifaceted cause. The exact etiology and pathogenesis of acne are yet to be established completely and various causative factors are considered as pathogenic mechanisms in the development of this disorder. We designed a study to determine the extent of serum trace elements, macrominerals and antioxidants in patients with acne, and thereby, to find the pathophysiological correlations, if any. Serum trace elements and macro-minerals were determined by flame atomic absorption spectroscopy. RP-HPLC was used to quantify antioxidants. Significantly (p